THE IMPACT OF D’BINGU PUDDING TO DECREASE BLOOD GLUCOSE LEVEL ON TYPE 2 OF DM PATIENT AT SOSIAL PUBLIC HEALTH CENTER PALEMBANG - Gipyapuri, Rhea Ajeng; Susyani,, Susyani,; Terati, Terati (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2019)
Diabetes Mellitus is a diseases metabolic characterized by hiperglikemia as a result of septal secrection of insulin, work insulin or both. It?s caused by unbalance intake of food that raising blood glucose levels. Low glycemic index and high fiber snacks are needed by the DM patient. The purpose is to identify the effect of d?bingu pudding in decreasing blood glucose level on DM outpatient type 2 at Sosial Public Health Center. The research type is quantitative research with quasi experiment design by using paired t-test and t-independen data analysis. The result is most of the action group have a low average of intake, which energy intake is 50%, carbohydrate intake is 50%, and fiber is 66.7%. The control group results are 53.3% of energy intake, 60% of carbohydrate intake, and 46.7% of fiber intake. The blood glucose difference for the action group is p-value 0.0000, and for the control group is p-value 0.011. The distribution of d?bingu pudding in decreasing of blood glucose level with p-value 0.000. The conclusion of this research is d?bingu pudding decrease the blood glucose on type 2 DM patient in Palembang social health center.